Using Mobile Airtime Credits to Incentivize Learning, Sharing and Survey Response: Experiences from the Field - Mehta, Devansh; Mothilal, Ramaravind K.; Sharma, Alok; Thies, Bill; Sharma, Amit (ACM COMPASS: Conference on Computing and Sustainable Societies, 2020)
In the Global South, mobile airtime payment has emerged as a popular way to incentivize different research studies, including ones on survey completion or disseminating information to people. Building on this literature, we report deployment experiences from three different studies in India that used airtime incentives. The first was used to promote awareness about HIV/AIDS, the second for promoting awareness and surveying preparedness for an upcoming election, and the third to measure learning and encourage people to vote in a conflict-hit region for a different election. Unlike past work, we found that a delivery mechanism that focuses on asking questions first, rather than presenting a tutorial and then asking questions, worked well in practice. In addition, we found multiple challenges in adoption of the technology and tried different ways to incentivize peer sharing of our system. Between the three deployments, we also addressed other technical and human-centered challenges such as delayed airtime payments and people using the system on behalf of someone else. We hope that our experiences and insights can be helpful to others seeking to deploy applications that utilize mobile airtime payments for learning, sharing, and survey response.